Differential metabolism of pectic galactan in tomato and strawberry fruit: detection of the LM26 branched galactan epitope in ripe strawberry fruit. Issue 1 (11th July 2018) - Posé, Sara; Marcus, Susan E.; Knox, J. Paul
Abstract : Antibody‐based approaches have been used to study cell wall architecture and modifications during the ripening process of two important fleshy fruit crops: tomato and strawberry. Cell wall polymers in both unripe and ripe fruits have been sequentially solubilized and fractions analyzed with sets of monoclonal antibodies focusing on the pectic polysaccharides. We demonstrate the specific detection of the LM26 branched galactan epitope, associated with rhamnogalacturonan‐I, in cell walls of ripe strawberry fruit. Analytical approaches confirm that the LM26 epitope is linked to sets of rhamnogalacturonan‐I and homogalacturonan molecules. The cellulase‐degradation of cellulose‐rich residues that releases cell wall polymers intimately linked with cellulose microfibrils has been used to explore aspects of branched galactan occurrence and galactan metabolism. In situ analyses of ripe strawberry fruits indicate that the LM26 epitope is present in all primary cell walls and also particularly abundant in vascular tissues. The significance of the occurrence of branched galactan structures in the side chains of rhamnogalacturonan‐I pectins in the context of ripening strawberry fruit is discussed.